Analysis of genetic diversity of African yam bean using SSR markers derived from cowpea - Shitta, N.S.; Abberton, Michael T.; Adesoye, A.I.; Adewale, D.B.; Oyatomi, Olaniyi (Cambridge University Press, 2016)
African yam bean, AYB (Sphenostylis stenocarpa Hochst. ex. A. Rich Harms), is a tuberous legume of tropical Africa. AYB has the potential to significantly boost food security due to its considerable nutritional qualities. However, the crop is underutilized. To efficiently utilize AYB genetic resources for its improvement, it is necessary to understand the crop’s diversity. This study investigated the amplification ability of 36 cowpea simple sequence repeat (SSR) primers across AYB genomic DNA, extracted from 67 accessions. Thirteen (36%) of the cowpea SSRs showed transferability in AYB. Eight of these SSRs amplified above 60% of AYB accessions and generated 55 polymorphic fragments with an average of 6.9 per primer. Polymorphic information content ranged from 0.6691 to 0.8857 with an average of 0.7791. This study also assessed the genetic diversity within 67 AYB accessions using eight cowpea (Vigna unguiculata L. Walp)-derived SSR primers. The result revealed a high level of genetic diversity with simple matching coefficient ranging from 0.458 to 1.000. A dendrogram depicting three main clusters was generated based on unweighted pair group method with arithmetic average. Cluster 1 was the most diverse with a dissimilarity range of 0.517–1.000. The level of genetic diversity revealed in this study indicates that the studied AYB germplasm can be exploited for genetic improvement. Additionally, the transferable markers will aid AYB genome research and also make possible the comparative mapping between AYB and cowpea.African yam bean, AYB (Sphenostylis stenocarpa Hochst. ex. A. Rich Harms), is a tuberous legume of tropical Africa. AYB has the potential to significantly boost food security due to its considerable nutritional qualities. However, the crop is underutilized. To efficiently utilize AYB genetic resources for its improvement, it is necessary to understand the crop’s diversity. This study investigated the amplification ability of 36 cowpea simple sequence repeat (SSR) primers across AYB genomic DNA, extracted from 67 accessions. Thirteen (36%) of the cowpea SSRs showed transferability in AYB. Eight of these SSRs amplified above 60% of AYB accessions and generated 55 polymorphic fragments with an average of 6.9 per primer. Polymorphic information content ranged from 0.6691 to 0.8857 with an average of 0.7791. This study also assessed the genetic diversity within 67 AYB accessions using eight cowpea (Vigna unguiculata L. Walp)-derived SSR primers. The result revealed a high level of genetic diversity with simple matching coefficient ranging from 0.458 to 1.000. A dendrogram depicting three main clusters was generated based on unweighted pair group method with arithmetic average. Cluster 1 was the most diverse with a dissimilarity range of 0.517–1.000. The level of genetic diversity revealed in this study indicates that the studied AYB germplasm can be exploited for genetic improvement. Additionally, the transferable markers will aid AYB genome research and also make possible the comparative mapping between AYB and cowpea.African yam bean, AYB (Sphenostylis stenocarpa Hochst. ex. A. Rich Harms), is a tuberous legume of tropical Africa. AYB has the potential to significantly boost food security due to its considerable nutritional qualities. However, the crop is underutilized. To efficiently utilize AYB genetic resources for its improvement, it is necessary to understand the crop’s diversity. This study investigated the amplification ability of 36 cowpea simple sequence repeat (SSR) primers across AYB genomic DNA, extracted from 67 accessions. Thirteen (36%) of the cowpea SSRs showed transferability in AYB. Eight of these SSRs amplified above 60% of AYB accessions and generated 55 polymorphic fragments with an average of 6.9 per primer. Polymorphic information content ranged from 0.6691 to 0.8857 with an average of 0.7791. This study also assessed the genetic diversity within 67 AYB accessions using eight cowpea (Vigna unguiculata L. Walp)-derived SSR primers. The result revealed a high level of genetic diversity with simple matching coefficient ranging from 0.458 to 1.000. A dendrogram depicting three main clusters was generated based on unweighted pair group method with arithmetic average. Cluster 1 was the most diverse with a dissimilarity range of 0.517–1.000. The level of genetic diversity revealed in this study indicates that the studied AYB germplasm can be exploited for genetic improvement. Additionally, the transferable markers will aid AYB genome research and also make possible the comparative mapping between AYB and cowpea.African yam bean, AYB (Sphenostylis stenocarpa Hochst. ex. A. Rich Harms), is a tuberous legume of tropical Africa. AYB has the potential to significantly boost food security due to its considerable nutritional qualities. However, the crop is underutilized. To efficiently utilize AYB genetic resources for its improvement, it is necessary to understand the crop’s diversity. This study investigated the amplification ability of 36 cowpea simple sequence repeat (SSR) primers across AYB genomic DNA, extracted from 67 accessions. Thirteen (36%) of the cowpea SSRs showed transferability in AYB. Eight of these SSRs amplified above 60% of AYB accessions and generated 55 polymorphic fragments with an average of 6.9 per primer. Polymorphic information content ranged from 0.6691 to 0.8857 with an average of 0.7791. This study also assessed the genetic diversity within 67 AYB accessions using eight cowpea (Vigna unguiculata L. Walp)-derived SSR primers. The result revealed a high level of genetic diversity with simple matching coefficient ranging from 0.458 to 1.000. A dendrogram depicting three main clusters was generated based on unweighted pair group method with arithmetic average. Cluster 1 was the most diverse with a dissimilarity range of 0.517–1.000. The level of genetic diversity revealed in this study indicates that the studied AYB germplasm can be exploited for genetic improvement. Additionally, the transferable markers will aid AYB genome research and also make possible the comparative mapping between AYB and cowpea.